Penerapan Motion Graphic Pada Animasi 2D Sirah Nabawiyah - Andra Hariadi Fernando; Sheanny Ocmi Sakti (Journal of Innovative and Creativity, 2025)
The study purpose was to explore the application of 2D motion graphic animation in the educational animation series "Sirah Nabawiyah," produced by Studio Piapi, aiming to enhance public understanding of the life and teachings of Prophet Muhammad SAW and to share practical experience in motion graphic animation as a learning resource for aspiring animators. Materials and methods involved a combination of creative design and animation techniques using 2D motion graphic tools, focusing on integrating graphic elements, text, and audio to create dynamic and engaging visual narratives. The study also involved reflection on the animator’s professional experience in the production process of the series. Results demonstrated that 2D motion graphic animation is effective in visualizing complex Islamic historical concepts simply and attractively, making the content accessible and educational for children and the wider community. The medium proved beneficial not only for communication but also for artistic expression aligned with cultural and religious values. Conclusions indicate that 2D motion graphic animation is a suitable and impactful media format for religious educational content like "Sirah Nabawiyah." It supports enhanced learning engagement, encourages value internalization, and offers a practical platform for training future motion graphic animators.